Mapping the role of official bioethics advice in the governance of biotechnologies in the EU: The European Group on Ethics’ opinion on commercial cord blood banking - Mohr, Alison; Busby, Helen; Hervey, Tamara; Dingwall, Robert (Oxford University Press, 2012)
In the early 1990s, the EU's proposed bioeconomic agenda provoked ethical concerns among its citizenry. In response to the political impasse between economic and ethical imperatives, as well as the perceived lack of democratic legitimacy, the EU established an expert bioethics advisory body, known as the European Group on Ethics in Science and New Technologies (EGE). Situated at the boundary between law, bioethics and economic policy, the EGE plays an ambiguous role in the governance of biotechnologies in the EU. To elucidate the nature of its role and influence, this paper considers the EGE as an integral element of a broader web of governance spanning EU and Member State institutions. Using as a case study the emerging controversy surrounding commercial cord blood banking, we explore whether the EGE and its ethical opinions on this matter have contributed to the democratic legitimacy of the EU.